The Effectiveness of Adding Rice Husk Nanosilica to the Flexural Strength of Opaque Porcelain Coatings on Metal Ceramic Dental Crowns - Nurul Fauziyah Zain; Sopan Sinamo; Elisanta Desriana Br Sinuraya; Florenly (HM Publisher, 2022)
Background. Failure of dentures that are unable to withstand flexural forces is often a major problem in the use of metal-ceramic crowns. The use of rice husk nano-silica powder has been extensively researched in dentistry because of its ability to improve mechanical properties. This study aims to determine the effectiveness of nano-silica particles from rice husks on the flexural strength of the opaque layer on Co-Cr metal-ceramic crowns. Methods. The type of research is experimental laboratories in vitro with posttest only control group design. The research samples were rectangular Co-Cr metal and porcelain plated on top of the metal center totaling 25 samples which were divided into 5 treatment groups. Flexural strength measurement with three-point bending at UTM. Data were analyzed by independent T-test and way ANOVA. Results. flexural strength of Co-Cr metal ceramic crown with the addition of 0.25% rice husk silica; 0.5%; 0.75%.1% in the opaque layer is 70.431±4.168; 84.093±2.852; 100,672±4,182 and 115,092±3,821, respectively. Conclusion. There is an increase in the flexural strength of metal ceramic crowns with the addition of 0.25% silica; 0.5%; 0.75%,1% on opaque coating.